The Impact of Supply Chain Integration via Mediator—Supply Chain Resilience—on Improvement in the Performance of Manufacturing Sectors - Omoush, Majd (International Review of Management and Marketing, 2025)
The aim of this study is to develop an integrated model of the economic value of the of the supply chain integration (SCI) through resilience, in Jordan’s manufacturing sector, focusing on how internal integration, supplier integration, and customer integration drive firm performance, with particular emphasis on the mediating effect of supply chain resilience. Data were collected from 300 managers of various manufacturing firms through a structured questionnaire, and linear regression and SEM were used to test the hypothesized relationships. The results indicated that internal integration significantly improves operational efficiency and cost reduction, supplier integration improves the efficiency of purchasing cost, and customer integration enhances responsiveness to market trends. Supply chain resilience is important in enabling firms to maintain stability in performance despite disruptions. The findings have implications for practical investment in integration and resilience to achieve strategic performance by Jordanian manufacturers. This research extends the literature on how SCI influences performance in a developing economy, with an emphasis on the need for a balanced approach between integration and resilience. Future studies should investigate these dynamics across different contexts to better comprehend the interplay between SCI and resilience.